2016
DOI: 10.1136/bmjopen-2016-011747
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic health expenditure according to employment status in South Korea: a population-based panel study

Abstract: ObjectivesCatastrophic health expenditure (CHE) means that the medical spending of a household exceeds a certain level of capacity to pay. Previous studies of CHE have focused on benefits supported by the public sector or high medical cost incurred by treating diseases in South Korea. This study examines variance of CHE in these households according to changes in employment status. We also determine whether a relationship exists according to income level.DesignA longitudinal study.SettingWe used the Korean Wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…We identified several determinants of CHE in this review, but it is worthy to note that household poverty/low socio‐economic status was the most common factor that increased CHE in six out of the eight studies that assessed determinants of CHE. Similarly, poverty has also been recognized as a determinant of CHE in other studies . This is especially so given that even small costs for common illnesses can be financially disastrous for poor households with no insurance cover .…”
Section: Discussionmentioning
confidence: 91%
“…We identified several determinants of CHE in this review, but it is worthy to note that household poverty/low socio‐economic status was the most common factor that increased CHE in six out of the eight studies that assessed determinants of CHE. Similarly, poverty has also been recognized as a determinant of CHE in other studies . This is especially so given that even small costs for common illnesses can be financially disastrous for poor households with no insurance cover .…”
Section: Discussionmentioning
confidence: 91%
“…On the other hand, two studies found that having insurance was a risk factor for incurring CHE (33, 44). Four studies reported that insurance does not have a significant effect on the occurrence of CHE (33, 35, 43, 46). Two of the studies on the situation in China both reported that the role of insurance depends on the type of insurance scheme that the household has; urban health insurance was found to be protective whereas rural health insurance was found to be a positive predictor that increases the risk of experiencing CHE (22, 39).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 25 studies investigated the relationship between family size and incurring CHE ( 15 , 16 , 18 22 , 24 28 , 31 – 43 ). Five studies found that the relationship is not significant ( 16 , 19 , 36 , 38 , 41 ), ten studies found that a large family size is a risk factor ( 18 , 20 , 22 , 24 , 26 , 31 , 32 , 34 , 35 , 40 ) and ten found that a small family size is associated with a higher risk ( 15 , 21 , 25 , 27 , 28 , 33 , 37 , 39 , 42 , 43 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Yang et al [9] found that catastrophic health expenditures have a high incidence among elderly households in China, and empty-nest households are at a higher risk for catastrophic health expenditures than non-empty-nest households. Moreover, Choi et al [10] found that for South Korea by using panel data low-income families with members who had either lost a job or were already unemployed are more likely to incur catastrophic health expenditure than those with family members with a consistent job.…”
Section: Introductionmentioning
confidence: 99%